Tulbaghia violacea Harv. Extracts Affect Key Intermediates of the Cryptococcus neoformans Ergosterol Biosynthetic Pathway - Benesh Munilal Somai; Mitradev Pattoo (International Journal of Phytomedicine, 2021)
This study investigated the mechanism of inhibition of Cryptococcus neoformans by Tulbaghia violacea plant extract. C. neoformans cultures were treated with sub-inhibitory concentrations of T. violacea extract and the effect of the exposure on the production of various sterol intermediates was analyzed by high performance reverse phase liquid chromatography. Plant extract treated C. neoformans cultures exhibited reductions in ergosterol production after 48 hrs of exposure in a dose dependent manner. HPLC analysis overall revealed an accumulation in squalene, 2,3-oxidosqualene and lanosterol intermediates after extract treatment. It is therefore concluded that T. violacea extract reduced ergosterol production in C. neoformans by interfering with squalene epoxidase, 2,3-oxidosqualene lanosterol cyclase and lanosterol 14-a demethylase. The inhibitory effect of T. violacea plant extract on ergosterol production in C. neoformans unlocks the potential of this extract as a chemotherapeutic agent.